2012
DOI: 10.12955/ejbe.v4i0.154
|View full text |Cite
|
Sign up to set email alerts
|

Impact Of Insurance On Economic Growth: The Case Of Republic Of Macedonia

Abstract: The purpose of this paper is to examine the impact of insurance and economic growth, with empirical analysis for the Republic of Macedonia. We apply multiple regression and control for other relevant determinants of economic growth. The analysis used data for the period 1995 - 2010. In order to solve the model in the analysis will use the technique of least squares, followed by analysis of variability in order to identify the effects of each variable. Insurance development is measured by insurance penetration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 11 publications
2
24
0
1
Order By: Relevance
“…For instance, on the one hand, a study by [18] shows a positive impact on economic growth by non-life insurance activity as measured by penetration rate but finds a negative effect on economic growth as measured by density 1 . On the other hand, [11] found a positive and significant effect of aggregate and non-life insurance activity on economic growth, while the relationship was negative for life insurance activity. A recent study by [19] in six countries which differed in terms of economic development showed a significant positive relationship between insurance penetration and per capita income.…”
Section: Studies Of the Relationship Between Insurance Activity And Ementioning
confidence: 83%
“…For instance, on the one hand, a study by [18] shows a positive impact on economic growth by non-life insurance activity as measured by penetration rate but finds a negative effect on economic growth as measured by density 1 . On the other hand, [11] found a positive and significant effect of aggregate and non-life insurance activity on economic growth, while the relationship was negative for life insurance activity. A recent study by [19] in six countries which differed in terms of economic development showed a significant positive relationship between insurance penetration and per capita income.…”
Section: Studies Of the Relationship Between Insurance Activity And Ementioning
confidence: 83%
“…Assessing the distance of the Ukrainian insurance market from other markets. 6. Determination of the level of openness of the insurance market of Ukraine on the basis of the law of gravity.…”
Section: Main Results Of Investigationmentioning
confidence: 99%
“…Thus, foreign scholars who were focused on the study of the openness of the financial market are Zhang, Z. [11], Xiangsheng Dou [10], Edwards S. [2], Quinn D., Inclan C. [6]. The authors whose works relate to the definition of the relationship between openness and the growth of the economy are Arena M. [1], Haiss P., Sumegi K. [3], Kjosevski J.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They argued that there was a positive impact of life insurance in GDP growth for the first group of countries, for the second group they found a greater impact on non-life insurance. Kjosevski, J (2011) discussed the impact of insurance on economic growth by using three variables: life insurance, non-life insurance, and full insurance coverage. He used data from the period of 1995-2010 of the Republic of Macedonia, using OLS technique, followed by a variability analysis to identify the effects of each variable.…”
Section: Literature Reviewmentioning
confidence: 99%